In formation one woman's rise through the ranks of the U.S. Air Force - Dietrich, Cheryl (Yucca, 2016)
"Documents the author's transformation from an out-of-shape introvert and military neophyte into one of the key personnel responsible for helping redesign the Air Force within the Pentagon, sharing insights into her particular challenges as a woman in a male-dominated section of the military, "--NoveList